Highly tough and elastic microspheric gel for transarterial catheter embolization in treatment of liver metastasis tumor. (21st March 2023) - Wang, Shuyun; Yu, Hongjie; Wan, Guangsheng; Fang, Haowei; Mi, Jinxia; Xu, Wenqian; Sun, Kexiang; Zhang, Kunxi; Yin, Jingbo; Deng, Wanli
Abstract: Transarterial embolization is a widely recognized clinical treatment method for liver tumors. Given that the soft and easily damaged features of embolic particles may limit tumor embolization efficiency, the present study carries out an attempt of fabricating tough and elastic microspheric gel for promoting embolization efficiency. To promote the toughness of hydrogel, poly(ethylene glycol)- co -poly(ε-caprolactone)- co -poly(ethylene glycol) (PPP) and PPP with two terminal double bonds (PPPDA) are co-assembled into nano-micelles, which are connected with methacrylated chitosan (CSMA) to fabricate microspheric gels via microfluidic technology. Lowering double bond density of micelles promotes the freedom degree of micelles, significantly enhancing hydrogel toughness. To compensate for the strength loss caused by the decrease of double bond density of micelles, phytic acid (PA) are employed to interact with CS to form a physical network, further improving hydrogel strength and toughness. The CS-PPPDA&PPP-PA microspheric gels exhibit higher blocking effect in vitro . A rabbit VX2 liver metastasis tumor model is prepared to verify the embolization efficacy of CS-PPPDA&PPP-PA microspheric gels. Compared with clinical used microspheres, fewer CS-PPPDA&PPP-PA microspheric gels can achieve enough embolization efficiency. After embolization for 14 days, CS-PPPDA&PPP-PA microspheric gels exhibit improved tumor necrosis rate and promoted tumor cells apoptosis with reduced inflammation in surrounding tissues, confirming advanced embolic efficiency of tough microgels. Graphical Abstract: